Pertumbuhan dan Produksi Dua Varietas Tomat (Lycopersicon esculentumMill.) secara Hidroponik dengan beberapa Komposisi Media Tanam - Endang Wijayanti; Anas D. Susila (Buletin Agrohorti, 2013)
The objectives of this researchwasto determine the effect of growing media composition on growth and production of two varieties of tomatoes in a hydroponic system. The research used Randomized Complate Block Design (RCBD) with two factors, they were tomato varieties and growing media composition. The tomato varieties were (Arthaloka, Permata) and growing media compotition were 100% husk (v/v), 75% husk + 25% bamboo leaves compost (v/v), 50% husks + 50% bamboo leaves compost (v/v), 25% husk + 75% bamboo leaves compost (v/v), and 100% bamboo leaves compost (v/v). Permata variety better than Arthaloka variety, based the higher number of flower and flower bunches, number of fruit, weight of fruit and grade of fruit. Bamboo leaves compost increased heigh of plant at 2-5 week after transplanting (WAT), number of leaves at 2-4 WAT, number of flower at 4-5 WAT, and 7-8 WAT, and number of flowers bunches at 5–11 WAT. The used of bamboo leaf compost 50% (v/v) and 75% (v/v) increased fruit number of tomato Permata variety at 7 WAT.Keywords: rice husk, bamboo leaf compost, hydroponics, tomato production